NURSING CARE IN THE PREVENTION OF MATERNAL DEATHS DUE TO POSTPARTUM HEMORRHAGE - Quirino Queiros, Yasmin; Baron Okimoto, Luisa; de Araújo Pereira, Luccas; Vieira de Oliveira, Lauanda; Khouri Fernandes, Rafaella; Xavier Valenzuela, Laura; Eduarda Sanchez Lino, Maria; Fernando Araújo Filho, Wagner; Isadora Ferreira Coelho, Bruna; Schmidt Cardoso de Souza, Marcele; Maria Félix Bonfim, Jéssica; Virginia Borges Souza de Aquino Coelho, Dioelen (Brazilian Journal of Implantology and Health Sciences, 2024)
Postpartum hemorrhage is the main complication that occurs during childbirth, and can lead to shock and consequently death, and appropriate treatment is essential. It is characterized by the loss of large amounts of blood after childbirth due to the lack of contraction of the uterus after the birth of the baby. Hemorrhage is considered when a woman loses 500 mL of blood after vaginal delivery or 1000 mL of blood after cesarean section and the main causes of postpartum hemorrhage are: tone, trauma, tissue and thrombin. The objective of the research was to gather evidence on the characteristics, prevention, treatment and factors that contribute to postpartum hemorrhage. A narrative literature review was carried out with data collection in the Virtual Health Library (BVS), Medical Literature Analysis and Retrieval System Online (Medline) and the National Library of Medicine (Pubmed), using the following descriptors in English: Postpartum hemorrhage, Prevention and control, Maternal death. The study highlighted the importance of preventing and treating the disease, including screening for risk factors through prenatal care.